(3GdNha GdeQVj dOi GdCWaGd (B:s (3GdJONd hGdYdGL (B/s - (3SYO, eQGO Ydj YjSis; (3GdeYQGL, SejQ YWjIs ((3OShb (B[(3eUQ(B] :s a, 2020)
(3jMJhj cJGH GdNha GdeQVj dOi GdCWaGd Ydi SJI aUhd jJfGhd GdaUd GdChd SjchdhLjI GdNha dOi GdEfSGf hCeG GdaUd GdKGfj jJfGhd GdNha YfO GdCWaGd hjJfGhd GdaUd GdKGdK GdNha GdGLJeGYj GdeQVj CeG GdaUd GdQGHY GdQGHY GdYdGL GdeYQaj GdSdhcj ddQgGH GdGLJeGYj hjJfGhd GdaUd GdNGeS GdYedjI GdYGeI ddYdGL GdeYQaj GdSdhcj hCNjQG GdaUd GdSGOS GdYdGL GdeYQaj GdSdhcj ddQgGH GdGLJeGYj dOi GdCWaGd(B.s
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3GdNha YfO GdCWaGds -- (3LhGfH faSjIs; (3GdCWaGds -- (3Yde faSs